Menu Close

tan-tan-3-1-tan-3-d-




Question Number 152273 by peter frank last updated on 27/Aug/21
∫ ((tan θ+tan^3 θ)/(1+tan^3 θ))dθ
tanθ+tan3θ1+tan3θdθ
Answered by qaz last updated on 27/Aug/21
∫((tan θ+tan^3 θ)/(1+tan^3 θ))dθ  =∫((tan θ)/(1+tan^3 θ))d(tan θ)  =∫((xdx)/(1+x^3 ))  =∫(x/((x+1)(x^2 −x+1)))dx  =(1/3)∫(((x+1)/(x^2 −x+1))−(1/(x+1)))dx  =(1/6)∫((2x−1+3)/(x^2 −x+1))dx−(1/3)∫(1/(x+1))dx  =(1/6)ln∣x^2 −x+1∣+(1/6)∙(1/(2∙(√(3/4))))tan^(−1) ((x−(1/2))/( (√(3/4))))−(1/3)ln∣x+1∣+C  =(1/6)ln∣((x^2 −x+1)/((x+1)^2 ))∣+(1/( 6(√3)))tan^(−1) ((2x−1)/( (√3)))+C  =(1/6)ln∣((tan^2 θ−tan θ+1)/((tanθ+1)^2 ))∣+(1/( 6(√3)))tan^(−1) ((2tan θ−1)/( (√3)))+C
tanθ+tan3θ1+tan3θdθ=tanθ1+tan3θd(tanθ)=xdx1+x3=x(x+1)(x2x+1)dx=13(x+1x2x+11x+1)dx=162x1+3x2x+1dx131x+1dx=16lnx2x+1+161234tan1x123413lnx+1+C=16lnx2x+1(x+1)2+163tan12x13+C=16lntan2θtanθ+1(tanθ+1)2+163tan12tanθ13+C

Leave a Reply

Your email address will not be published. Required fields are marked *